THE EFFECT OF ENTREPRENEURS SCALE, LONG ENTREPRENEURSHIP ON THE EXISTENCE OF MSMEs DURING PANDEMIC - Aris Indriyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The Indonesian economy is currently experiencing a bit of a drag due to the pandemic. The existence of this pandemic has made several sectors in Indonesia experience a significant impact, especially in the field, especially MSMEs. This study aims to determine the effect of entrepreneurial scale, duration of entrepreneurship and the existence of MSMEs that can survive during the pandemic. The data collection technique in this study was using a questionnaire. Data analysis using multiple regression model with the help of SPSS analysis. The sampling method for this study was guided by the determination of the number of samples as many as 50 MSME owners. The instrument testing technique in this research is validity and reliability test, regression test, hypothesis test in the form of t test, F test and determination test. The results showed that partially, scale entrepreneurs (X1)and the number of entrepreneurs (X2 ) positive and significant effect on the existence of the SMEs especially true in times of pandemic.Therefore, parties who have an interest in increasing micro-enterprises, especially the Department of Industry, Trade and Cooperatives in the City of Yogyakarta, increase the scale of entrepreneurship and duration of entrepreneurship so that MSMEs can maintain their existence during Pandemic.